Desain Alat Monitoring Jarak Jauh Mesin Genset 300 kVA Berbasis IoT - Al Qurniafan Hadi Jaya; Zakiyah Amalia (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
A 300 kVA generator set is an important tool as a backup power source in many sectors. Manual monitoring of generator set performance is often inefficient and can cause delays in detecting problems. Various advances in Internet of Things (IoT) technology have enabled the design of remote monitoring systems to overcome these limitations. This study aims to develop an IoT-based monitoring tool capable of monitoring important generator set parameters such as voltage, current, power, and engine temperature in real-time. This will enhance generator set management efficiency and reduce the risk of damage. The method used is an experimental approach involving the creation of an IoT-based monitoring system prototype. Operational data from the generator set is collected using sensors and then transmitted to an IoT platform for analysis. This research uses PZEM-004T sensors to monitor parameters such as power, current, and voltage. RTD PT100 sensors monitor parameters such as engine temperature, oil temperature, and turbo temperature. Honeywell PX3 sensors monitor oil pressure. Honeywell 1GT101DC sensors monitor engine speed. The results of the study show that the device works well with an average error of 0.76% from the sensors used. The greater the distance between the Wi-Fi modem and the device, the slower the data response speed.